Improving Students’ Skills Of Writing Scientific Articles Through ‘One Semester One Book’ Writing Program - Ibda, Hamidulloh; Wahyuningsih, Effi (International Journal of English Education and Linguistics (IJoEEL), 2019)
Writing scientific articles for higher education students, especially undergraduate ones will be difficult without habituation, training, and program with product oriented in form of book. If it runs naturally and lecturers only give assignments to write scientific articles without education or literacy education, they tend to make plagiarism. This study aims at improving the students’ skills of writing scientific articles through ‘One Semester One Book’ writing program. Classroom activity is designed as the pillar of literacy namely reading, writing, and arithmetic in accordance with the integrated language learning approach by combining four language skills which is oriented by product of articles or book. The results of the study show that there are improvements of the students’ scientific articles writing skills achieved by 89 students in some aspects. They cover the progress of: first, skills of determining the research problems from 35 students (39%) to 85 students (95%); second, skills of determining the theme and tittle of the scientific articles from 24 students (26%) to 89 (100%); third, skills of determining the word choice appropriately from 25 students (28%) to 80 students (89%); fourth, skills of using correct spelling based on General Indonesian Spelling Guidelines (PUEBI) rules from 35 students (39%) to 75 students (84%); fifth, skills of applying citation method from 25 students (28%) to 80 students (89%); sixth, improvement of the number of the students who do not commit plagiarism from 25 students (28%) to 85 students (95%); and seventh, skills of writing contemporary issues about education or religion from 34 students (38%) to 84 students (94%). The research findings reveal that the ‘One Semester One Book’ writing program is strategic in improving the students’ skills of writing scientific articles.